Legal Analysis of Indonesian River Management and Flood Management Policy - Astoni, Punta Yoga (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2025)
State control over rivers based on Article 33 of the 1945 Constitution of the Republic of Indonesia affirms the State’s role as regulator, manager, and guarantor of public welfare through water resources governance. Rivers constitute strategic natural resources because they traverse multiple administrative areas and influence ecosystem balance across regions. However, declining river carrying capacity—driven by spatial planning changes, environmental degradation, and uncontrolled human activities—can trigger flooding disasters with significant social, economic, and environmental impacts. Therefore, flood risk management must be implemented in an integrated manner through river and watershed (DAS) policies that address both flood magnitude reduction and vulnerability reduction. This study applies normative legal research using statutory, historical, and conceptual approaches to examine flood management policies in Indonesia. The findings indicate that river governance should be oriented toward sustainability, community participation, and social justice to achieve long-term public welfare.